Kekosongan Hukum Dalam Penilaian Letak Kerugian Pada Kepentingan Umum atau Kepentingan Militer Sebagai Dasar Kewenangan Peradilan Koneksitas - Novritsar Hasintongan Pakpahan; Yulinda Regina C. Lumban Gaol (Sanskara Hukum dan HAM, 2022)
Connectivity trial (or known as conflicting trials in US) are regulated by Section 89 sub-section (1) of Act 8 of 1981 on Criminal Procedure or KUHAP. This regulation determines when it is necessary to conduct a trial involving the general and military environments to examine a criminal case. The determination of which environment will become the parent court is based on discussions between the prosecutor's office and the military prosecutor as referred to in Section 91 sub-section (1) of KUHAP. However, in the practice of these discussions, there is no legal provision regarding the point of emphasis. Finally, the discussion is prone to not finding a middle point and will fall into an agency feud. For this reason, it is necessary to have legal certainty in determining losses to determine losses. This research was conducted with the aim of finding legal answers to how the legal basis for the assessment of losses to determine the authority of the connectivity trial. The research method used is in the form of normative research with a conceptual approach, statutory approach, and case study approach. The results of this study found that the assessment of losses that can be used to provide legal certainty is an assessment of losses for the costs incurred and the real costs of repairing the impact of criminal acts.